A Bibliometric Approach on RetirementInvestment Studies (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Financial planning necessitates a comprehensive  assessment of an individual's current and future financial circumstances. This study aims  to review and assess the existing literature on retirement financial planning with 9397  research. While financial planning, in general,  has received substantial attention, retirement specific planning remains fragmented and  limited.The available literature is disjointed,  predominantly subjective, and narrow in scope.  Notably, despite a recent surge in research  prompted by the pandemic, investment and  financial planning remain underrepresented  in conjunction with retirement and pension  keywords. This study offers valuable insights  for academics and policymakers to identify  areas necessitating further research in retirement  financial planning.
Keywords: Bibliometric; Financial Planning; Investment; Retirement; Saving